2018
DOI: 10.1038/s41598-018-23426-y
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and damage-free outgassing of implanted helium from amorphous silicon oxycarbide

Abstract: Damage caused by implanted helium (He) is a major concern for material performance in future nuclear reactors. We use a combination of experiments and modeling to demonstrate that amorphous silicon oxycarbide (SiOC) is immune to He-induced damage. By contrast with other solids, where implanted He becomes immobilized in nanometer-scale precipitates, He in SiOC remains in solution and outgasses from the material via atomic-scale diffusion without damaging its free surfaces. Furthermore, the behavior of He in SiO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 53 publications
2
11
0
Order By: Relevance
“…In contrast to the high density of He bubbles in implanted Fe films, no helium bubbles (>1 nm) were observed in pure SiOC film after 5 at% He implantation, Figure 2c,d. This result was consistent with previous finding that He atoms in SiOC remain in solution and are able to outgas from the material via atomic-scale diffusion [15,28]. In addition, the irradiation does not lead to any void formation, element segregation or crystallization throughout the SiOC film.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast to the high density of He bubbles in implanted Fe films, no helium bubbles (>1 nm) were observed in pure SiOC film after 5 at% He implantation, Figure 2c,d. This result was consistent with previous finding that He atoms in SiOC remain in solution and are able to outgas from the material via atomic-scale diffusion [15,28]. In addition, the irradiation does not lead to any void formation, element segregation or crystallization throughout the SiOC film.…”
Section: Resultssupporting
confidence: 92%
“…While the above discussion on interface design strategies have shown that it is possible to delay the deleterious effects of He, recent studies have shown that in some materials it is possible to avert helium bubble formation entirely by continually removing it as it is implanted [15]. Amorphous SiOC, a new class of superior radiation tolerant materials, has shown very good steady-state irradiation properties [16].…”
Section: Introductionmentioning
confidence: 99%
“…This observation is consistent with our previous studies, where no He bubbles were observed in amorphous SiOC films subjected to an applied implantation dose of up to 113 at. % 13 , 19 . In contrast to the absence of He bubbles in the implanted SiOC film, the under-focused TEM micrograph of the implanted Fe film (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Another example of an amorphous material with unique irradiation/implantation stability is amorphous silicon oxycarbide (SiOC). Our previous studies on SiOC demonstrated that He bubble formation can be entirely averted due to the rapid diffusion of implanted ions out of the structure 13 , 19 . It was also demonstrated that amorphous/crystalline nanolaminates consisting of amorphous SiOC/crystalline α-Fe have desirable structural stability over a range of irradiation/implantation conditions (i.e., ion species, energy, and temperature) 20 23 .…”
Section: Introductionmentioning
confidence: 99%
“…This model class of amorphous ceramics has exhibited great stability under irradiation, sustaining its glassy state over a wide range of irradiation conditions [14,15]. In addition, it has demonstrated the immunity of He bubble formation by continually removing He as it was implanted [16,17]. For instance, implanted He atoms were found to outgas from the SiOC matrix through atomic-scale diffusion without damaging its free surfaces, even at liquid nitrogen temperatures, resulting in time-invariant structure and properties.…”
Section: Introductionmentioning
confidence: 99%